2013
DOI: 10.1128/jvi.03159-12
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Encoded MicroRNA BART15-3p Promotes Cell Apoptosis Partially by Targeting BRUCE

Abstract: b Epstein-Barr Virus (EBV) generates a variety of viral microRNAs (miRNAs) by processing the BHRF1 and BamHI A rightward (BART) transcripts. BART miRNAs are expressed in all cells latently infected with EBV, but the functions of most BART miRNAs remain unknown. The results of a cell proliferation assay revealed that miR-BART15-3p inhibited cell proliferation. Fluorescence-activated cell sorting following staining with annexin V or propidium iodide showed that miR-BART15-3p promoted apoptosis. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 41 publications
2
83
0
Order By: Relevance
“…Antisense knockdown of TOMM22 has been shown to inhibit the association of the pro-apoptotic protein Bcl-2-associated X (BAX) with mitochondria and thus prevent BAX-induced apoptosis (Bellot et al, 2007;Dolken et al, 2010). MiR-BART15-3p can induce apoptosis partially by inhibiting an apoptosis inhibitor, BIR repeatcontaining ubiquitin-conjugating enzyme (BRUCE) (Choi et al, 2013). These reports show that EBV miRNAs help to maintain the viral latent status in the infected cells by preventing the host immune response.…”
Section: Ebv Mirnas Suppress Apoptosis Of Infected Cells To Maintain mentioning
confidence: 83%
See 1 more Smart Citation
“…Antisense knockdown of TOMM22 has been shown to inhibit the association of the pro-apoptotic protein Bcl-2-associated X (BAX) with mitochondria and thus prevent BAX-induced apoptosis (Bellot et al, 2007;Dolken et al, 2010). MiR-BART15-3p can induce apoptosis partially by inhibiting an apoptosis inhibitor, BIR repeatcontaining ubiquitin-conjugating enzyme (BRUCE) (Choi et al, 2013). These reports show that EBV miRNAs help to maintain the viral latent status in the infected cells by preventing the host immune response.…”
Section: Ebv Mirnas Suppress Apoptosis Of Infected Cells To Maintain mentioning
confidence: 83%
“…EBV-transformed lymphoblastoid B cells also secrete several viral miRNAs, including miR-BHRF1-1, miR-BHRF1-2, miR-BART1-3p, miR-BART1-5p, and miR-BART2-5p (Meckes et al, 2010). EBV-infected B lymphocytes are able to secrete miR-BART15 (Choi et al, 2013). The exosomal miR-BART15 provides a favorable microenvironment for the growth of EBV-associated tumors.…”
Section: Ebv Regulates the Inflammatory Tumor Microenvironment Via MImentioning
confidence: 99%
“…For example, Marquitz et al demonstrated that the expression of the proapoptotic protein Bim was downregulated by several EBV miRNAs located in ebv-miR-BART cluster 1, to which ebv-miR-BART4-5p belongs (29). Several miRNAs in cluster 1 have been demonstrated to show both antiapoptotic and proapoptotic effects, and it is possible that several EBV miRNAs interact to cooperatively regulate apoptosis via different apoptosis-related proteins (30,36,37). Further work is necessary to clarify the complex mechanism by which EBV miRNAs regulate apoptosis-related proteins and the potential relationship with latent genes and tumor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr Virus (EBV) microRNAs (miRNAs) processed from the BHRF1 and BamHI A rightward (BART) transcript, miR-BART15-3p, targets the 3' untranslated region (UTR) of BIRC6. miR-BART15-3p inhibits the translation of BIRC6 protein in EBV-infected gastric carcinoma cells and contributes to host cells apoptosis induction (Choi et al, 2013). In muscle, prostaglandin F2a upregulates BIRC6 which promotes muscle cell survival and growth (Jansen and Pavlath, 2008).…”
Section: Regulation Of Birc6mentioning
confidence: 99%